To Sedate or Not to Sedate? Lessons Learned from a Novel Pediatric Simulation-Based Training Curriculum for Procedural Sedation Privileges in Acute Care Pediatricians. Issue Volume 34:Issue s1(2019) (May 2019) - Severin, Paul; Robin, Beverley
Abstract : Aim: To develop a simulation-based pediatric procedural sedation curriculum for acute care attending physicians to achieve and maintain privileges in this important skill. Methods: Neonatal and pediatric intensive care physicians participated in simulation-based sedation training to achieve and maintain sedation privileges. Participants were required to review pediatric sedation materials prior to participation. Demographic data were collected prior to the simulations, and all participants completed a pre-test to assess their baseline knowledge. Sessions were held in the simulation center or neonatal intensive care unit (depending on group), and the attending physicians, in pairs, participated in two high-fidelity mannequin scenarios (sedation for a painful procedure; hypoxia during sedation). Simulations were followed by a facilitated debriefing session while utilizing a standard performance checklist. All participants completed a program evaluation at the conclusion of their training. Results: Neonatal (n=11) and pediatric (n=9) intensive care attending physicians participated in the sedation simulation training. The program was well received and 100% rated it as "excellent" or "very good". All participants strongly agreed the instructors allotted time for questions/answers, 100% strongly agreed the debriefing/feedback was effective, 95% strongly agreed instructors had a thorough knowledge and understanding of the program, were supportive, and facilitated learning, and 95% strongly agreed the equipment and physical environment were conducive to learning. Participants reported that simulation-based training and the use of a standardized checklist during facilitated debriefing were very helpful and effective for sedation training. Additionally, many participants indicated the desire for more simulation-based training. Discussion: Simulation-based sedation training is a feasible, easy to implement, and viable learning technique for acute care physicians.